(untitled) (Journal of Bangladesh Academy of Sciences, 2010)
Asymptotic solutions for stationary and non-stationary modes for the upper and lower branch disturbances assuming large scale magnetic fields are investigated. A triple deck structure which governs the lower branch modes for a large scale magnetic field is displayed. The wavenumbers and waveangle calculated from the eigenrelations α ≈ 2.62m5/4r-1/2, β ≈ 0.78 m1/4 r1/2, φ = 0.298m-1r, to be consistent with the numerical results for large scale magnetic fields. Key words: Magnetic field; Instability; Rotating-disk flow DOI: 10.3329/jbas.v34i1.5491 Journal of Bangladesh Academy of Sciences, Vol.34, No.1, 49-58, 2010